Performance of dual-form Terminalia catappa organic fertilizers on sweet corn yield and economic viability in tropical highlands - Sari, Stefina Liana; Solihin, Eso; Budiarto, Rahmat (Kultivasi, 2026)
Recycling underutilized plant biomass into organic fertilizers underpins low-input cropping strategies, but liquid and solid formulations derived from a common feedstock have seldom been evaluated side by side under field conditions. This study aimed to (i) characterize the physicochemical properties and safety profile of a liquid organic fertilizer (LOF) and a crumb-type organic fertilizer (COF) co-produced from Terminalia catappa leaf compost, (ii) compare their effects on sweet corn growth and yield, (iii) determine relative agronomic effectiveness (RAE), and (iv) evaluate economic feasibility of the most promising organic–inorganic combinations. We produced LOF and COF through aerobic composting of Terminalia catappa leaves (60%), black soldier fly (Hermetia illucens) larval frass (20%), and livestock manure (20%); the LOF was recovered as composting leachate and the COF as the dried, friable compost residue. Laboratory characterization confirmed that both products met Indonesian national quality standards (SNI 8167:2015 and SNI 7763:2024), with heavy metals and microbial contaminants well below permissible limits. Two parallel field trials were then conducted (November 2025–February 2026) on a volcanic Andisol near Lembang, West Java (ca. 1,200 m a.s.l.) using sweet corn cv. Paragon. Each trial followed a randomized complete block design with seven treatments and four replicates. LOF at one dose (50 L ha⁻¹) combined with only one-quarter of the standard NPK achieved the highest husked-ear yield (8,500 kg ha⁻¹, relative agronomic effectiveness/RAE = 250%) and the most favorable benefit–cost ratio (B/C = 1.21). COF at one dose (1,000 kg ha⁻¹) with half the standard NPK yielded 16,849 kg ha⁻¹ (RAE = 154%, B/C = 1.61). The two formulations require distinct integration strategies: LOF can substitute up to 75% of mineral NPK, whereas COF performs best at 50% replacement. These findings support the valorization of T. catappa leaf litter into dual-form organic fertilizers for tropical highland sweet corn systems.